Failure study of Sn37Pb PBGA solder joints using temperature cycling, random vibration and combined temperature cycling and random vibration tests. (December 2018) - An, Tong; Fang, Chao; Qin, Fei; Li, Huaicheng; Tang, Tao; Chen, Pei
Abstract: In this paper, the tin-lead (Sn-37wt%Pb) eutectic solder joints of plastic ball grid array (PBGA) assemblies are tested using temperature cycling, random vibrations, and combined temperature cycling and vibration loading conditions. The fatigue lives, failure modes for the solder joints and the typical locations of the failed solder joints for single-variable loading and combined loading conditions are compared and analyzed. The results show much earlier solder joint failure for combined loading than that for either temperature cycling or pure vibration loading at room temperature. The primary failure mode is cracking within the bulk solder under temperature cycling, whereas the crack propagation path is along the intermetallic compound (IMC) layer for vibration loading. The solder joints subjected to combined loading exhibit both types of failure modes observed for temperature cycling and vibration loading; in addition, cracking through the IMC and the bulk solder is observed in the combined test. For temperature cycling and vibration loading, the components in the central region of the printed circuit board (PCB) have more failed solder joints than other components, whereas for combined loading, the number of failed solder joints in the components in different locations of the PCB is approximately the same. Graphical abstract: Highlights: Temperature cycling, random vibration and combined loading tests were conducted on Sn37Pb soldered PBGA assemblies. The fatigue lives of the solder joints subjected to multiple environmental loading conditions were compared and discussed. The location of the failed solder joints for single loading and combined loading conditions are discussed.